Insights into the Oxidation State and Location of Rhenium in Re‐Pd/TiO2 Catalysts for Aqueous‐Phase Selective Hydrogenation of Succinic Acid to 1, 4‐Butanediol as a Function of Palladium and Rhenium Deposition Methods. Issue 14 (3rd June 2015) - Ly, Bao Khanh; Tapin, Benoît; Aouine, Mimoun; Delichere, Pierre; Epron, Florence; Pinel, Catherine; Especel, Catherine; Besson, Michèle
Abstract ReOx‐Pd/TiO2 catalysts prepared from different 2 wt %Pd/TiO2 catalysts using two protocols for the deposition of the Re promoter (successive impregnation and catalytic reduction) were characterized by different techniques to better understand the nature of the active and selective sites implied in the aqueous‐phase hydrogenation of succinic acid to 1, 4‐butanediol. Regardless of the support and Re introduction method, it was established that varying amounts of Pd and Re were in very close proximity without electronic interaction in the reduced catalysts. A high fraction of Re always remained partially oxidized to generate a bimetallic catalyst that can provide the necessary bifunctional sites to enable the selective hydrogenolysis of the intermediate γ‐butyrolactone to 1, 4‐butanediol. Depending on the method of promotion, the ReOx species that interact with Pd were deposited as clusters with different spatial Re–Re interactions.